Sandwiching textiles with FDM Printing - Mahmut-Sami Özev; Andrea (Communications in Development and Assembling of Textile Products)
3D printing on textile fabrics has been investigated intensively during the last years. A critical factor is the adhesion between the printed polymer and the textile fabric, limiting the potential areas of application. Especially safety-related applications, e.g. stab-resistant textile/polymer composites, need to show reliable adhesion between both components to serve their purpose. Here we investigate the possibility of sandwiching textiles between 3D-printed layers, produced by fused deposition modeling (FDM). We show that adding nubs to the lower 3D-printed layers stabilizes the inner textile fabric and suggest future constructive improvements to further enhance the textile-polymer connection.